2019
DOI: 10.3389/fimmu.2019.01924
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Angiogenesis With Peptide Vaccines

Abstract: Most cancer peptide vaccinations tested so far are capable of eliciting a strong immune response, but demonstrate poor clinical benefits. Since peptide vaccination is safe and well-tolerated, and several indications suggest that it has clear potential advantages over other modalities of treatment, it is important to investigate the reasons for these clinical failures. In this review, the current state of the art in targeting angiogenic proteins via peptide vaccines is presented, and the underlying reasons for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Although our research demonstrated that the expression and secretion of VEGFA was regulated by LBH in glioma cell lines and GSCs, the exact transcriptional mechanism of LBH on VEGFA requires further study. Moreover, VEGF is a vital treatment target for anti-tumor therapy, and there are several VEGF-targeting drugs, such as bevacizumab [46,47]. It is possible that patients with increased LBH expression may be sensitive to anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although our research demonstrated that the expression and secretion of VEGFA was regulated by LBH in glioma cell lines and GSCs, the exact transcriptional mechanism of LBH on VEGFA requires further study. Moreover, VEGF is a vital treatment target for anti-tumor therapy, and there are several VEGF-targeting drugs, such as bevacizumab [46,47]. It is possible that patients with increased LBH expression may be sensitive to anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to overcome this, Mabs can be attached to a nanocarrier surface via a pre-adsorption process and prevent biomolecular corona formation [ 190 , 191 ]. The nature of HGG, mainly GBM cells, which are incredibly heterogenic, makes the usage of monovalent vaccines inadequate to control tumor progression [ 192 , 193 , 194 ]. For example, some peptide vaccines are vastly restricted towards the EGFR V III variant, which is only present in 23–33% of GBM patients [ 195 , 196 ].…”
Section: Drug Development For Hgg: Advancements and Challengesmentioning
confidence: 99%
“…Both autoreactive immune cells and their secreted cytokines can result in harmful autoreactive immune attacks towards host cells and tissues, and thus, they are the two main targets for immunotherapy in rheumatic diseases. Distinct forms of peptide-based vaccinations have been studied for therapeutic or preventive strategies for diseases such as cancer, rheumatic diseases, and allergic disorders [34][35][36][37][38]. According to the therapeutic targets, peptide-based vaccinations used for rheumatic diseases can be classified into two main subtypes including peptide-based active vaccination against pathogenic cytokines and peptide-based tolerogenic vaccination.…”
Section: Types Of Peptide-based Vaccination Therapymentioning
confidence: 99%
“…Many peptide autoepitopes have been proven to be involved in the pathogenesis of SLE [167][168][169]. Some histone peptides such as histone H4 autoepitope peptide 16-39 (H4 ) and autoepitope peptide 71-94 (H4 ) could induce an inflammatory response, whereas others such as H2A [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] could lead to an immunosuppressive response [167,168]. Therefore, different peptides can lead to distinct immune response during the development of SLE.…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%